2023
DOI: 10.1097/bpo.0000000000002419
|View full text |Cite
|
Sign up to set email alerts
|

Patient Adherence to Wide Abduction Brace Treatment for Legg-Calvé-Perthes Disease

Abstract: Background: A wide abduction brace called the A-frame brace is used to contain the deformed femoral head and improve femoral head remodeling in patients with Legg-Calvé-Perthes disease (LCPD). While there is some data showing the efficacy of brace treatment, little is known about patient adherence. The purpose of this study was to measure A-frame brace adherence using temperature sensors and to identify factors that influence adherence. Methods: This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It is worth noting that Kim HKW 's latest study aimed at measuring the brace adherence of the A-frame, an equipment used to contain the deformed femoral head and improve femoral head remodeling in patients with LCPD using temperature sensors, and to identify factors that influence adherence. The study found that the compliance of A-frame braces was significantly associated with age at the time of treatment, previous Petrie casting, and daily prescribed brace wear ( 23 ). This latest study provides new insights and suggestions for the treatment and prevention of LCPD.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that Kim HKW 's latest study aimed at measuring the brace adherence of the A-frame, an equipment used to contain the deformed femoral head and improve femoral head remodeling in patients with LCPD using temperature sensors, and to identify factors that influence adherence. The study found that the compliance of A-frame braces was significantly associated with age at the time of treatment, previous Petrie casting, and daily prescribed brace wear ( 23 ). This latest study provides new insights and suggestions for the treatment and prevention of LCPD.…”
Section: Discussionmentioning
confidence: 99%